2011
DOI: 10.1097/qad.0b013e32834b95bf
|View full text |Cite
|
Sign up to set email alerts
|

A plasma microRNA signature of acute lentiviral infection

Abstract: Objective Plasma microRNAs are modulated during disease and are emerging biomarkers; they have not been characterized in HIV infection. Using our macaque/simian immunodeficiency virus (SIV) model of HIV, we sought to identify a plasma miRNA profile of acute lentiviral infection, evaluate its relationship with known cellular and viral determinants of lentivirus-associated CNS disease, and explore the potential of miRNAs to predict CNS disease. Design Plasma samples were obtained pre-inoculation and ten days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 90 publications
2
84
0
Order By: Relevance
“…Previous studies have shown that HIV infection leads to distinct changes in miRNA expression profiles in cell lines and PBMCs from HIV-infected patients (14,(52)(53)(54)(55). MicroRNA have also been reported to disrupt viral replication and are thought to be involved in establishing viral latency (11,14,56).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HIV infection leads to distinct changes in miRNA expression profiles in cell lines and PBMCs from HIV-infected patients (14,(52)(53)(54)(55). MicroRNA have also been reported to disrupt viral replication and are thought to be involved in establishing viral latency (11,14,56).…”
Section: Discussionmentioning
confidence: 99%
“…C T values from the QuantStudio machine that did not exceed 35 (the array-wide validated limit of quantitation) were exported using ExpressionSuite (Life Technologies) software. Quantile normalization for arrayed data was performed as has been previously described using the limma package, version 3.24.3, in R (www .r-project.org), version 3.1.2 (29)(30)(31).…”
Section: Methodsmentioning
confidence: 99%
“…These findings also suggest that the protective effects of cannabinoids may also be mediated by similar regulatory factors/mechanisms (epigenetic) that need to be further investigated and identified, especially as they relate to HIV infection. For instance, several in vitro studies have shown altered miRNA expression in response to HIV infection (30)(31)(32)(33)(34), and recent miRNA profiling studies performed on brain (35) and plasma samples (36) provide strong evidence of their dysregulation during SIV infection. In addition, we recently reported miR-190b to be significantly upregulated in the intestine at all stages of SIV infection (37) and that viral replication rather than infection-related inflammatory responses induced miR-190b upregulation (37).…”
mentioning
confidence: 99%